The Ribosomal DNA Loci of the Ancient Monocot Pistia stratiotes L. (Araceae) Contain Different Variants of the 35S and 5S Ribosomal RNA Gene Units - Anton Stepanenko (2022)
The freshwater plant water lettuce (Pistia stratiotes L.) grows in warm climatic zones and is used for phytoremediation and biomass production. P. stratiotes belongs to the Araceae, an ecologically and structurally diverse early monocot family, but the phylogenetic relationships among Araceae members are poorly understood. Ribosomal DNAs (rDNAs), including the 35S and 5S rDNA, encode the RNA components of ribosomes and are widely used in phylogenetic and evolutionary studies of various plant taxa. Here, we comprehensively characterized the chromosomal locations and molecular organization of 35S and 5S rDNA genes in water lettuce using karyological and molecular methods. Fluorescence in situ hybridization revealed a single location for the 35S and 5S rDNA loci, each on a different pair of the species’ 28 chromosomes. Molecular cloning and nucleotide sequencing of 35S rDNA of P. stratiotes, the first representative Araceae sensu stricto in which such a study was performed, displayed typical structural characteristics. The full-length repeat showed high sequence conservation of the regions producing the 18S, 5.8S, and 25S rRNAs and divergence of the internal transcribed spacers ITS1 and ITS2 as well as the large intergenic spacer (IGS). Alignments of the deduced sequence of 18S rDNA with the sequences available for other Araceae and representatives of other clades were used for phylogenetic analysis. Examination of 11 IGS sequences revealed significant intra-genomic length variability due to variation in subrepeat number, with four types of units detected within the 35S rDNA locus of the P. stratiotes genome (estimated size 407 Mb/1C). Similarly, the 5S rDNA locus harbors gene units comprising a conserved 119-bp sequence encoding 5S rRNA and two types of non-transcribed spacer (NTS) sequences.